Late‐onset anorectal disease and psychosocial impact in survivors of childhood cancer: A report from the Childhood Cancer Survivor Study. Issue 21 (19th July 2019) - Madenci, Arin L.; Dieffenbach, Bryan V.; Liu, Qi; Yoneoka, Daisuke; Knell, Jamie; Gibson, Todd M.; Yasui, Yutaka; Leisenring, Wendy M.; Howell, Rebecca M.; Diller, Lisa R.; Krull, Kevin R.; Armstrong, Gregory T.; et al.
Abstract : Background: The prevalence and associated psychosocial morbidity of late‐onset anorectal disease after surgery and radiotherapy for the treatment of childhood cancer are not known. Methods: A total of 25, 530 survivors diagnosed between 1970 and 1999 (median age at cancer diagnosis, 6.1 years; age at survey, 30.2 years) and 5036 siblings were evaluated for late‐onset anorectal disease, which was defined as a self‐reported fistula‐in‐ano, self‐reported anorectal stricture, or pathology‐ or medical record–confirmed anorectal subsequent malignant neoplasm (SMN) 5 or more years after the primary cancer diagnosis. Piecewise exponential models compared the survivors and siblings and examined associations between cancer treatments and late‐onset anorectal disease. Multiple logistic regression with generalized estimating equations was used to evaluate associations between late‐onset anorectal disease and emotional distress, as defined by the Brief Symptom Inventory 18 (BSI‐18), and health‐related quality of life, as defined by the Medical Outcomes Study 36‐Item Short Form Health Survey (SF‐36). Results: By 45 years after the diagnosis, 394 survivors (fistula, n = 291; stricture, n = 116; anorectal SMN, n = 26) and 84 siblings (fistula, n = 73; stricture, n = 23; anorectal neoplasm, n = 1) had developed late‐onset anorectal disease (adjusted rate ratio [RR] for survivors vs siblings, 1.2; 95% confidence interval [CI], 1.0‐1.5). Among survivors, pelvic radiotherapy with ≥30 Gy within 5 years of the cancer diagnosis was associated with late‐onset anorectal disease (adjusted RR for 30‐49.9 Gy vs none, 1.6; 95% CI, 1.1‐2.3; adjusted RR for ≥50 Gy vs none, 5.4; 95% CI, 3.1‐9.2). Late‐onset anorectal disease was associated with psychosocial impairment in all BSI‐18 and SF‐36 domains. Conclusions: Late‐onset anorectal disease was more common among childhood cancer survivors who received higher doses of pelvic radiotherapy and was associated with substantial psychosocial morbidity. Abstract : Late‐onset anorectal disease in survivors of childhood cancer is more common among survivors with a history of higher dose pelvic radiotherapy. Those survivors who develop anorectal disease have significant psychosocial morbidity in comparison with survivors who do not.